2018
DOI: 10.1253/circj.cj-18-0709
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Computed Tomography-Derived Abdominal Fat Area on Transcatheter Aortic Valve Implantation

Abstract: there have been no reports on the individual prognostic value of body fat. The aim of the present study was therefore to evaluate the effect of abdominal fat on long-term clinical outcomes in patients undergoing TAVI. To clarify this, we focused on abdominal fat area, including the visceral fat area (VFA) and subcutaneous fat area (SFA) evaluated on computed tomography (CT), and evaluated their individual effects on long-term clinical outcomes such as all-cause mortality and re-hospitalization due to worsening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…This is considered to be due to a patient's diminished physiological reserve, which is expressed as frailty. Previously, many frailty factors such as body mass index, subcutaneous fat area, gait speed, and multidimensional geriatric assessments have been reported to be useful for risk stratification of these high-risk patients [4][5][6][7][8][9]. Our results showed that objective nutritional indexes such as the CONUT score and PNI might also be useful to assess a patient's frailty and for risk stratification.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This is considered to be due to a patient's diminished physiological reserve, which is expressed as frailty. Previously, many frailty factors such as body mass index, subcutaneous fat area, gait speed, and multidimensional geriatric assessments have been reported to be useful for risk stratification of these high-risk patients [4][5][6][7][8][9]. Our results showed that objective nutritional indexes such as the CONUT score and PNI might also be useful to assess a patient's frailty and for risk stratification.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the CONUT score and PNI had better predictive values than GNRI. Malnutrition, which was evaluated by the CONUT score, PNI, or GNRI, is known to be well associated with frailty, and its correlation with prognosis in various diseases has been shown in previous reports [2][3][4][5][6][7][8][9][10][11]. Shibata et al have reported that GNRI is an important surrogate marker for predicting worse clinical outcomes even in patients undergoing TAVI [23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the utility of contrast enhanced scans (CES) for body composition analysis with the possibility of comparing the obtained values to other studies would be most convenient as many patients require a CES for other aspects of clinical decision making. Some studies already utilize fat segmented from CES for risk assessment, but comparing these results to those of previous works would only be possible with severe limitations (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…33 Because SFA and VFA, which contribute to AC, are considered to be important indicators, SFA and/or VFA may be more important markers than AC. 34,35 The volume of SF that can accumulate is predetermined and varies according to the individual. When this limit is exceeded, adipocytes will accumulate as VF.…”
Section: Discussionmentioning
confidence: 99%